2019
DOI: 10.4314/sokjvs.v17i1.6
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of viral skin diseases of cattle, sheep and goats in Plateau State, Nigeria

Abstract: Viral skin diseases namely lumpy skin disease (LSD), bovine papilloma (BP), goat pox (GTP) and contagious ecthyma (CE) have been reported in Plateau State, but our search through literatures did not reveal any documented prevalence rates of these diseases. A retrospective study of LSD, BP, GTP and CE was carried out based on Jos abattoir (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) and laboratory records of National Veterinary Research Institute, Vom, Nigeria (2010-2016. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In the first stage, three States in northern Nigeria were purposely selected (Bauchi, Plateau and Kaduna – Fig. 1 b) based on previous research showing that SGP was present in the area ( Adedeji et al, 2019 ; Ifende et al, 2019 ; Limon et al, 2020 ) and a history of SGP outbreaks reported to local veterinarians in recent years. In each State, an official list of LGAs was obtained and within each LGA, the list of village areas and, where available, their village heads.…”
Section: Methodsmentioning
confidence: 99%
“…In the first stage, three States in northern Nigeria were purposely selected (Bauchi, Plateau and Kaduna – Fig. 1 b) based on previous research showing that SGP was present in the area ( Adedeji et al, 2019 ; Ifende et al, 2019 ; Limon et al, 2020 ) and a history of SGP outbreaks reported to local veterinarians in recent years. In each State, an official list of LGAs was obtained and within each LGA, the list of village areas and, where available, their village heads.…”
Section: Methodsmentioning
confidence: 99%
“…Plateau State is located between 9.2° and 9.4°N, and between 9.3° and 9.4°E (Ifende et al, 2019). Majority (60%) of the State's human population (3.5 million people) practice poultry production where birds are raised in commercial, backyard and free-range systems (Wungak et al, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Lumpy skin disease is endemic but neglected disease of cattle in Nigeria. This study was designed in response to repeated outbreaks of (Gambo et al, 2018;Ifende et al, 2019). The study identifies the epidemiological features and economic impact of LSD on subsistence smallholder cattle farmers in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity is usually around 10 -14% while mortality ranges between 1% and 5% in endemic areas (Babiuk et al, 2008;Adedeji et al, 2017;Ochwo et al, 2020). The characteristic clinical signs of LSD include lacrimation, fever (40-41℃), lymphadenopathy and nodular skin lesions that progress to sitfast lesions, which can persist for many months (Babiuk et al, 2008;Adedeji et al, 2019). In some LSD outbreaks, affected animals develop swelling of one or more legs, lameness and edema of the dewlap (Tuppurainen et al, 2005;Tuppurainen & Oura, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation